2013
DOI: 10.1111/jocn.12063
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and usage of cancer screening among West African migrant women

Abstract: Nurses who encounter West African migrant women in their day-to-day practice have the opportunity to provide this group with education related to the importance of cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…In addition, a study in NSW reported that general practitioners (GPs) of different nationalities had varying attitudes to bowel cancer screening, and that GPs overall were less likely to recommend screening to immigrants [56]. Immigrant groups with lower screening rates come from countries where cancer screening is not highly diffuse or where there is an expectation that health professionals are responsible for recommending any test use [57,58,59,60,61,62]. Additionally, immigrants were found to have poorer knowledge of bowel cancer and screening tests, lesser intent to participate in screening practises and received fewer screening recommendations from GPs than Australian-born people [63].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study in NSW reported that general practitioners (GPs) of different nationalities had varying attitudes to bowel cancer screening, and that GPs overall were less likely to recommend screening to immigrants [56]. Immigrant groups with lower screening rates come from countries where cancer screening is not highly diffuse or where there is an expectation that health professionals are responsible for recommending any test use [57,58,59,60,61,62]. Additionally, immigrants were found to have poorer knowledge of bowel cancer and screening tests, lesser intent to participate in screening practises and received fewer screening recommendations from GPs than Australian-born people [63].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the final model, this factor was significant only for Kurdish women. Women who do not use reproductive health services might need more information on the importance of screening [21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Its incidence is rising among African women and their mortality rate is significantly higher compared to women in developed countries [1, 2]. Despite the fact that breast cancers in African women present at a younger age and at later stage [3, 4], research has demonstrated that both in their home countries and also in many Western countries, the participation of African women in breast cancer screening measures is poor [57]. …”
Section: Introductionmentioning
confidence: 99%